Prevention measures against occupational exposure of the nursing staff to antineoplastic agents: critical analysis (Research, Society and Development, 2021)
This study aims to search the scientific literature for evidence related to effective preventive measures against occupational exposure of the nursing staff to antineoplastic agents during nursing care for cancer patients. This is a literature review of scientific productions on the subject indexed, in the last 5 years, in electronic databases. Occupational exposure to antineoplastics can occur at different stages, in handling, when this is performed by the nurse, during transport, administration and contact with body fluids and secretions up to 48 hours after the end of the chemotherapy cycle. More generally, exposure can occur with environmental contamination, due to improper disposal, effective measures to prevent occupational exposure were considered to be the use of PPE for professionals who are in direct care, training in the area and about risks to which they are exposed and the existence of spill kits in the units where the procedures are carried out.